A mathematical model for assessing shear induced bleeding risk. (April 2023) - Li, Yuan; Wang, Hongyu; Xi, Yifeng; Sun, Anqiang; Wang, Lizhen; Deng, Xiaoyan; Chen, Zengsheng; Fan, Yubo
Highlights: Building a new mathematical model to predict bleeding risk in VAD and ECMO. Modeling variation between platelet-vWF binding ability to characterize bleeding risk. Predicted bleeding risk in HVAD > heartmate II, consistent with clinical statistics. Narrow and turbulence regions in devices are important contributions for bleeding. Abstract: Purpose: The objective of this study is to develop a bleeding risk model for assessing device-induced bleeding risk in patients supported with blood contact medical devices (BCMDs). Methods: The mathematical model for evaluating bleeding risk considers the effects of shear stress on von Willebrand factor (vWF) unfolding, high molecular weight multimers-vWF (HMWM-vWF) degradation, platelet activation and receptor shedding and platelet-vWF binding ability. Functions of the effect of shear stress on the above factors are fitted/employed and solved by the Eulerian transport equation. An axial flow-through Couette device and two clinical VADs which are HeartWare Ventricular Assist Device (HVAD) and HeartMate II (HM II) blood pump were employed to perform the simulation to evaluate platelet receptor shedding (GPIbα and GPIIb/IIIa), loss of HWMW-vWF, platelet-vWF binding ability and bleeding risk for validating the accuracy of our model. Results: The platelet-vWF binding ability after being subjected to high shear region in the axial flow-through Couette device predicted by our bleeding model was highly consistent with reported experimental data. As indicated by our CFD simulation results in the axial flow-through Couette device, it can find that an increase in shear stress led to a decrease in the adhesion ability of platelets on vWF, while the binding ability of vWF with platelets first increase and then decrease as shear stress elevates gradually beyond a threshold. The factor of exposure time can enhance the effect of shear stress. Additionally, the shear-induced bleeding risk predicted by our model increases with increasing shear stress and exposure time in an axial flow-through Couette device. As indicated by our numerical model, the bleeding risk in HVAD was higher than HMII, which is highly consistent with the meta-analysis based on clinical statistics. Our simulation investigations in these two clinical VADs also found that HVAD caused a higher rate of platelet receptor shedding and lower damage to HWMW-vWF than HeartMate II. The high shear stress generated in the narrow and turbulent regions of both VADs was the underlying cause of device-induced bleeding. Conclusion: In this study, the shear-induced bleeding risk predicted by our bleeding model in axial flow-through Couette device and two clinical VADs is consistent or highly correlated with experimental and clinical findings, which proves the accuracy of our bleeding model. Our bleeding model can be used to aid the development of new BCMDs with improved functional characteristics and biocompatibility, and help to reduce risk of device-induced adverse events in patients.